Dry masterbatch independent of substrate and having lfp or lmfp positive electrode particles
Patent Information
- Application Number
- CN202611111298.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-07-25
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]惟此种方式须多烘烤及辗压两步骤,制造成本较高,且在辗压的过程中,可能会导致该正极浆料层内的材料破碎,从而降低整个电池的性能
[0007]Currently, battery materials have gradually evolved from liquid batteries to solid or semi-solid batteries. Based on their long-term experience in the field of battery materials, the inventors of this case have proposed a novel dry masterbatch that is independent of the substrate and has LFP or LMFP positive electrode particles. This masterbatch utilizes the thermoplastic properties of PEO (Poly(ethylene oxide), polyoxyethylene), so that the positive electrode slurry does not need to be a solvent-containing positive electrode slurry when it is coated on the positive electrode substrate. Therefore, the subsequent baking and rolling steps can be omitted, reducing two steps in the process, resulting in lower overall costs and more stable battery material performance.
Smart Images

Figure CN122930904A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode slurry technology, and more particularly to a dry masterbatch that is independent of the substrate and has LFP or LMFP cathode particles. Background Technology
[0002] A conventional positive electrode material includes: a positive electrode comprising: a positive electrode substrate; a positive electrode slurry layer coated on the positive electrode substrate, wherein the positive electrode slurry layer is composed of a positive electrode slurry comprising: a plurality of positive electrode particles for storing or releasing lithium ions; a polymer material comprising PVDF (Polyvinylidene Fluoride); a solvent for dispersing the materials in the positive electrode slurry; a plurality of conductive agents; and a plurality of ceramic particles for guiding lithium ions and dispersing the lithium ion pathway.
[0003] In the conventional art, during the manufacturing process of the positive electrode slurry, the solvent is added to ensure that the material in the positive electrode slurry can be fully and uniformly dispersed. The positive electrode slurry containing the solvent is then coated onto the positive electrode substrate, and then baked to remove the solvent. Since the evaporation of the solvent will cause the positive electrode slurry layer to be filled with pores, it is necessary to roll it to ensure that the positive electrode slurry layer is tightly bonded to the positive electrode substrate.
[0004] However, this method requires two additional steps: baking and rolling, which increases the manufacturing cost. Furthermore, the rolling process may cause the material within the positive electrode slurry layer to break, thereby reducing the overall performance of the battery. Summary of the Invention
[0005] Therefore, the purpose of this invention is to solve the problems of the prior art. This invention proposes a dry masterbatch that is independent of the substrate and has LFP or LMFP positive electrode particles. The PEO is thermoplastic and melts into a molten state at high temperatures. Therefore, by utilizing the thermoplasticity of PEO to coat the molten positive electrode slurry onto the positive electrode substrate, it is not necessary to bake and roll it separately like conventional positive electrode slurries with solvents. This method can reduce the need for drying steps and avoid material breakage that may be caused by rolling. In addition, the electrode plates formed in this way have a longer shelf life.
[0006] To achieve the above objectives, this invention proposes a dry masterbatch independent of the substrate and containing LFP or LMFP positive electrode particles. The masterbatch is independent of the positive electrode substrate and is a separately carried material. In application, the masterbatch is melted at high temperature and bonded to the positive electrode substrate, thus forming the positive electrode plate. A typical solid-state or near-solid-state battery includes a positive electrode, which comprises: a positive electrode substrate, a carrier material for supporting the positive electrode; and a positive electrode slurry layer coated on the positive electrode substrate to form the positive electrode plate. The positive electrode slurry layer is composed of a positive electrode slurry, which is in the form of a masterbatch. The masterbatch is a solid material structure at room temperature. It comprises: multiple positive electrode particles for storing or releasing lithium ions, wherein each positive electrode particle is an active material; wherein the multiple positive electrode particles are selected from lithium manganese iron phosphate or lithium iron phosphate particles; PEO; the PEO is thermoplastic and melts at high temperatures; the PEO also has ion-conducting properties, therefore it can be used as a lithium ion conductor, increasing the overall lithium ion conduction capacity of the positive electrode; PVDF or PVDF-HFP; the PVDF and PEO are polymer materials; wherein when the masterbatch is heated to a certain temperature, the masterbatch... The PEO and PVDF-HFP / PVDF copolymer in the mixture are in a molten state, making the entire masterbatch sticky and adhering to the positive electrode substrate, forming the positive electrode plate as a whole; multiple conductive agents are used to increase the electronic conductivity of the positive electrode slurry; lithium salt is used to slide the molecular chains within the polymer material, thereby improving ionic conductivity; multiple ceramic particles are used to guide lithium ions, and these ceramic particles have high ionic conductivity for lithium ions; by guiding the multiple dispersed ceramic particles, abnormal accumulation of lithium ions in the positive electrode slurry is avoided. The positive electrode slurry produces a side reaction; wherein the plurality of positive electrode particles, the plurality of composite ceramic particles, the conductive agent and the lithium salt are dispersed among the polymer material used to support the entire positive electrode slurry; the masterbatch formed by the above materials is independent and portable, so the manufacturing of the masterbatch and the manufacturing of the electrode plate can be carried out separately; wherein, in the manufacturing of the electrode plate, the masterbatch is melted at high temperature and bonded to the positive electrode substrate, thus forming the positive electrode plate; due to the constituent materials of the masterbatch, the bonding process does not require drying and rolling procedures, and the masterbatch is directly attached to the positive electrode substrate.
[0007] Currently, battery materials have gradually evolved from liquid batteries to solid or semi-solid batteries. Based on their long-term experience in the field of battery materials, the inventors of this case have proposed a novel dry masterbatch that is independent of the substrate and has LFP or LMFP positive electrode particles. This masterbatch utilizes the thermoplastic properties of PEO (Poly(ethylene oxide), polyoxyethylene), so that the positive electrode slurry does not need to be a solvent-containing positive electrode slurry when it is coated on the positive electrode substrate. Therefore, the subsequent baking and rolling steps can be omitted, reducing two steps in the process, resulting in lower overall costs and more stable battery material performance.
[0008] The features and advantages of the invention will be further understood from the following description, and please refer to the accompanying drawings while reading. Attached Figure Description
[0009] Figure 1 This is a structural diagram of the case.
[0010] Figure 2 This shows a cross-sectional view of the composite ceramic particles in this case.
[0011] Among them, the conductive agent is 13, the positive electrode particles are 15, the polymer material is 17, the lithium salt is 19, the positive electrode is 20, the positive electrode substrate is 21, the masterbatch is 22, the positive electrode slurry layer is 23, the ceramic particles are 100, the composite layer is 110, the dopamine layer is 120, the PVDF layer is 130, the secondary composite particles are 140, and the composite conductive particles are 150. Detailed Implementation
[0012] The following is a detailed description of a preferred embodiment of the present invention, in conjunction with the accompanying drawings, regarding its structural composition, effects, and advantages.
[0013] Please refer to Figures 1 to 2 As shown, the dry masterbatch of the present invention, independent of a substrate and having LFP or LMFP positive electrode particles, is generally used in solid-state or near-solid-state batteries, which includes a positive electrode 20 comprising: A positive electrode substrate 21 is a carrier plate used to support the positive electrode 20; wherein the positive electrode substrate 21 is an aluminum foil substrate. A positive electrode slurry layer 23 is coated on the positive electrode substrate 21 to form a positive electrode plate. In this case, the positive electrode slurry layer 23 is composed of the masterbatch 22, which is independent of the positive electrode substrate 21 and is a separately carried material; in application, the masterbatch 22 is melted at high temperature and bonded to the positive electrode substrate 21, thus forming the positive electrode plate; The masterbatch 22 contains: Multiple positive electrode particles 15 are used to store or release lithium ions. These multiple positive electrode particles 15 are selected from lithium cobalt oxide (LCO) particles, single-crystal or polycrystalline nickel cobalt manganese (NCM) particles, and lithium manganese iron phosphate (LMFP) or lithium iron phosphate (LFP), etc.; preferably, the single-crystal nickel cobalt manganese particles are selected from NCM811 or NCMN9. The positive electrode particles 15 are an active material, and their proportion in the entire masterbatch 22 is between 88wt% and 97wt%.
[0014] PEO (Poly(ethylene oxide)) is thermoplastic and melts at high temperatures. It also possesses ion-conducting properties, thus it can be used as a lithium-ion conductor, increasing the overall lithium-ion conductivity of the cathode. PVDF (Polyvinylidene Fluoride) or PVDF-HFP (Poly(vinylidenefluoride-co-hexafluoropropylene)) wherein the PEO, PVDF or PVDF-HFP are polymer materials 17.
[0015] Due to the thermoplasticity of PEO, the masterbatch 22 can be deposited on the positive electrode substrate 21 in a liquid-like molten state at high temperatures. Therefore, it replaces the solvent added to the traditional positive electrode slurry. Replacing the solvent avoids the subsequent baking and rolling steps, reduces manufacturing costs, and prevents the positive electrode slurry layer 23 from breaking due to rolling. In addition, the electrode plate formed in this way has a longer shelf life.
[0016] The polymer material 17 further includes either PVA (Polyvinyl alcohol) or HDPE (High-Density Polyethylene).
[0017] The PVA and PEO are compatible, which reduces the possibility of material crystallization within the masterbatch 22 and improves the bonding between the masterbatch 22 and the positive electrode substrate 21. The HDPE has high toughness, which improves the strength and toughness of the positive electrode plate.
[0018] The PEO is thermoplastic and melts into a molten state at high temperatures. Therefore, by utilizing the thermoplasticity of PEO to coat the molten masterbatch 22 onto the positive electrode substrate 21, it is not necessary to bake and roll it separately, unlike conventional positive electrode slurries containing solvents. This method can reduce the need for drying steps and avoid material breakage that may be caused by rolling.
[0019] Multiple conductive agents 13 are selected from at least one of carbon nanotubes, amorphous carbon, and graphene. The amorphous carbon may be, for example, superP. The conductive agents 13 are used to increase the electronic conductivity of the masterbatch 22.
[0020] This masterbatch 22 also contains: Lithium salt 19 is used to improve electrochemical properties.
[0021] The lithium salt 19 is selected from either PDDA-TFSI (poly(diallyl dimethyl ammonium)-bis(trifluoromethanesulfonyl)imide) or Py14-TFSI (N-methyl-N-butylpyrrole bis(trifluoromethanesulfonyl)imide). PDDA-TFSI or Py14-TFSI can cause the molecular chains within the polymer material 17 to slide, thereby enhancing ionic conductivity.
[0022] The lithium salt 19 may also include at least one of LiBOB (lithium bis(oxalatoborate)), Li3PO4 (lithium phosphate), LiFSI (Lithium Bis(fluorosulfonyl)imide), LiTFSI (LiN(CF3SO2)2, lithium bis(trifluoromethylsulfonyl)amino), and LiPF6 (lithium hexafluorophosphate).
[0023] The LiTFSI is used to increase lithium-ion conductivity, while the LiBOB is used to prevent LiTFSI from being corroded by water and to prevent attack by HF (hydrofluoric acid) generated from the reaction of water and LiTFSI, which would lead to a decrease in the overall battery performance. It also allows the lithium salt 19 to withstand higher voltage differences, thus making the polymer material 17 relatively stable under the high voltage of the positive electrode 20. The addition of LiBOB increases overall stability.
[0024] Multiple ceramic particles 100 are used to guide lithium ions, and these ceramic particles 100 have high ionic conductivity for lithium ions. Therefore, when lithium ions pass through the positive electrode 20, the lithium ion pathway can be dispersed by the guidance of the multiple dispersed ceramic particles 100, avoiding abnormal accumulation of lithium ions in the masterbatch 22 and preventing side reactions with the masterbatch 22.
[0025] like Figure 1 As shown, the plurality of positive electrode particles 15, the plurality of composite ceramic particles 100, the conductive agent 13 and the lithium salt 19 are dispersed among the polymer material 17 used to support the entire masterbatch 22.
[0026] The weight ratio of the plurality of positive electrode particles 15 to the polymer material 17 and the lithium salt 19 to the conductive agent 13 and the plurality of ceramic particles 100 is 88~97:10~2:2~1, that is, the ratio of the plurality of positive electrode particles to the polymer material and the lithium salt to the conductive agent and the plurality of ceramic particles is A:B:C, where A ranges from 88 to 97; B ranges from 10 to 2; and C ranges from 2 to 1. Ratios of A, B, and C within these ranges are acceptable in this case. Numerical values used in the same way in this document have the same definition.
[0027] like Figure 2 As shown, the outer surface of each ceramic particle 100 may be coated with a composite layer 110, the composite layer 110 including a dopamine layer 120 coated on the outer surface of the ceramic particle 100, the dopamine layer 120 and the corresponding ceramic particle 100 forming a primary and secondary composite particle 140; wherein the dopamine layer 120 is composed of polydopamine molecules; and a PVDF layer 130 coated on the outer surface of the secondary composite particle 140, the PVDF layer 130 and the corresponding secondary composite particle 140 forming a composite guiding particle 150; wherein the PVDF layer 130 is composed of PVDF material; the PVDF material of the PVDF layer is formed during the manufacturing of the composite guiding particle 150, and is not formed by reaction with PVDF or PVDF-HFP in the masterbatch 22. The dopamine layer 120 does not completely cover the outer surface of the ceramic particle 100, so a small portion of the surface of the ceramic particle 100 will still be exposed; therefore, the PVDF layer 130 will partially contact the surface of the ceramic particle 100 and partially contact the dopamine layer 120. In the PVDF material of the PVDF layer 130, some of the fluoride ions will form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles 100 to form lithium fluoride; while another part of the fluoride ions in the PVDF material of the PVDF layer 130 will form hydrogen bonds with the nitrogen ions of the polydopamine molecules on the surface of the secondary composite particles 140. Therefore, the PVDF material will form the PVDF layer 130 covering the outer surface of the secondary composite particles 140.
[0028] The ceramic particles 100 are lithium-ion conductive (ionic conductivity greater than 10). -5 cm 2Oxides with a diffusion coefficient of / s (diffusion coefficient), or oxides or sulfides with garnet or perovskite structures. Examples of oxides with lithium-ion conductivity include lithium aluminum germanium phosphate (LAGP) and lithium aluminum titanium phosphate (LATP) with a NASICON (sodium (Na) super ionic conductor) structure; examples of oxides with garnet or perovskite structures include lithium lanthanum zirconium oxide (Li7La3Zr2O). 12 The sulfide is such as LPSC (LPSCl, sulfide solid electrolyte), and the ceramic particles 100 are selected from at least one of the above materials.
[0029] When the ceramic particles 100 are composed of LLZO material, the LLZO material is selected from at least one of LLZO, Ga-LLZO (Ga-doped LLZO, gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (Cu-doped LLZO, copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (Ta-doped LLZO, tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (Sr-doped LLZO, strontium-doped lithium lanthanum zirconium oxide), and Al-LLZO (Al-doped LLZO, aluminum-doped lithium lanthanum zirconium oxide).
[0030] When the ceramic particles are composed of LAGP, the LAGP is selected from Li 1+x Al x Ge 2-x (PO4)3 or Li 1+x+ y Al x Ge 2-x-y-z M y N z (PO4)3; When the ceramic particles are composed of LATP, the LATP is selected from Li 1+x Al x Ti 2-x (PO4)3, or Li 1+x+y Al x Ti 2-x-y-z M y N z(PO4)3; where x is between 0.1 and 0.8, y is between 0 and 0.2, and z is between 0 and 0.2; where M is a trivalent cation, such as Sc 3+ (scandium ion), Y 3+ (yttrium ions), Ga 3+ (Gallium ions), In 3+ (Indium ion), La 3+ (Lanium ion), etc.; where N is a tetravalent cation, such as Zr. 4+ (zirconium ions), Si 4+ (silicon ions), Sn 4+ (Tin ions), etc.
[0031] In actual use, the masterbatch 22 is a solid material structure at room temperature. When the masterbatch 22 is heated to a certain temperature (between 50°C and 240°C), the PEO, the lithium salt, and the copolymer formed by PVDF-HFP or PVDF in the masterbatch 22 will be in a molten state, making the entire masterbatch 22 sticky, so that it can be attached to the positive electrode substrate 21, thereby forming the positive electrode plate.
[0032] In conventional techniques, a traditional positive electrode paste is coated onto the positive electrode substrate 21. This conventional positive electrode paste contains a solvent, so after coating, subsequent drying and rolling processes are required to form a positive electrode paste layer attached to the substrate 21. This method involves two additional processing steps, resulting in higher costs. The masterbatch 22, however, utilizes the molten property of PEO at high temperatures to adhere to the positive electrode substrate 21. It does not require the addition of a solvent to bond with the substrate 21. Therefore, when the masterbatch 22 is applied to the positive electrode substrate 21, the drying and rolling processes are unnecessary, reducing manufacturing costs. Furthermore, because the masterbatch 22 is a solid material structure, the manufacturing of the positive electrode plate is not limited by the requirement that the traditional positive electrode paste and the positive electrode substrate 21 must be manufactured simultaneously. The masterbatch 22 in this invention is readily available and can be stored at room temperature, making the manufacturing of the positive electrode plate more flexible. Because the masterbatch is formed from the aforementioned material and is independent and portable, the manufacturing of the masterbatch and the electrode plate can be carried out separately and independently.
[0033] In the masterbatch 22, multiple positive electrode particles 15 are mainly used as active particles to store or release lithium ions; the polymer material 17 is used to disperse and adhere the materials in the masterbatch 22. In order to enable the lithium ions in the masterbatch 22 to conduct rapidly and achieve high battery electrical conductivity, multiple ceramic particles 100 are added to the masterbatch 22. When lithium ions pass through the positive electrode 20, the multiple dispersed ceramic particles 100 can guide the lithium ion pathway, avoiding abnormal accumulation of lithium ions in the masterbatch 22 and preventing side reactions with the masterbatch 22. The polymer material 17 has a relatively low lithium ion conductivity. Therefore, in order to increase lithium ion conductivity, lithium salt 19 is added to the polymer material 17, which can increase the overall lithium ion density. This allows lithium ions to quickly enter and exit when there is a potential difference between the two ends of the masterbatch 22, thereby increasing the lithium ion conduction speed. In order to improve the overall efficiency of lithium ions, in addition to increasing the lithium ion conduction speed, the electron conduction is also very important. Therefore, adding the conductive agent 13 to the masterbatch 22 can increase the electron conduction force.
[0034] The advantage of this invention is that PEO is thermoplastic and melts into a molten state at high temperatures. Therefore, by utilizing the thermoplasticity of PEO to coat the molten positive electrode slurry onto the positive electrode substrate, it is not necessary to bake and roll it separately, unlike conventional positive electrode slurries with solvents. This method not only reduces the need for drying steps and avoids material breakage that may be caused by rolling, but also results in a longer shelf life for the electrode plate formed in this way.
[0035] In conclusion, the thoughtful and user-friendly design in this case is highly in line with actual needs. Its specific improvements over existing deficiencies represent a significant breakthrough compared to prior art, offering genuine functional enhancements that are not easily achieved. Furthermore, since this case has not been publicly disclosed or revealed in domestic or international literature or markets, it complies with patent law requirements.
[0036] The above detailed description is a specific description of a feasible embodiment of the present invention. However, this embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the spirit of the present invention should be included in the patent scope of this case.
Claims
1. A dry masterbatch independent of a substrate and having LFP or LMFP positive electrode particles, characterized in that, The masterbatch is independent of the positive electrode substrate and is a separately carried material. In application, the masterbatch is melted at high temperature and bonded to the positive electrode substrate to form a positive electrode plate. The masterbatch comprises: Multiple positive electrode particles are used to store or release lithium ions, wherein the positive electrode particle is an active material; wherein the multiple positive electrode particles are selected from lithium manganese iron phosphate or lithium iron phosphate particles. PEO; PEO is thermoplastic and melts at high temperatures; PEO also has ion-conducting properties, so it can be used as a lithium-ion conductor to increase the overall lithium-ion conductivity of the cathode. PVDF or PVDF-HFP; the PVDF and the PEO are polymer materials; when the masterbatch is heated to a certain temperature, the PEO and the copolymer of PVDF-HFP / PVDF in the masterbatch will be in a molten state, making the entire masterbatch sticky and adhering to the positive electrode substrate, thus forming the positive electrode plate as a whole. Multiple conductive agents; these multiple conductive agents are used to increase the electronic conductivity of the masterbatch; Lithium salts are used to slide the molecular chains within the polymer material, thereby enhancing its ionic conductivity. Multiple ceramic particles are used to guide lithium ions. These ceramic particles have high ionic conductivity for lithium ions. By guiding the lithium ions through multiple dispersed ceramic particles, abnormal accumulation of lithium ions within the masterbatch and side reactions with the masterbatch are avoided. The plurality of positive electrode particles, the plurality of composite ceramic particles, the conductive agent and the lithium salt are dispersed among the polymer material used to support the entire masterbatch; The masterbatch formed by the above materials is independent and portable, so the manufacturing of the masterbatch and the manufacturing of the electrode plates can be carried out separately and independently; In the manufacturing of the electrode plate, the masterbatch is melted at high temperature and bonded to the positive electrode substrate to form the positive electrode plate. Due to the composition of the masterbatch, there is no need to go through the drying and rolling process during the bonding process, and the masterbatch is directly attached to the positive electrode substrate.
2. The dry masterbatch as described in claim 1, characterized in that, Each ceramic particle is further coated with a composite layer, which includes a dopamine layer covering the outer surface of the ceramic particle, forming a primary and secondary composite particle with the corresponding ceramic particle; wherein the dopamine layer is composed of polydopamine molecules; and a PVDF layer covering the outer surface of the secondary composite particle, forming a composite conductive particle with the corresponding secondary composite particle; wherein the PVDF layer is composed of PVDF material; wherein the dopamine layer does not completely cover the outer surface of the ceramic particle, so a small portion of the surface of the ceramic particle remains exposed; therefore, the PVDF layer partially contacts the surface of the ceramic particle, and partially contacts the dopamine layer. In the PVDF material of the PVDF layer, some of the fluoride ions will form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles to form lithium fluoride; while another part of the fluoride ions in the PVDF material of the PVDF layer will form hydrogen bonds with the nitrogen ions of the polydopamine molecules on the surface of the secondary composite particles. Therefore, the PVDF material will form the PVDF layer covering the outer surface of the secondary composite particles.
3. The dry masterbatch as described in claim 1 or 2, characterized in that, The ceramic particles are oxides with lithium-ion conductivity, or oxides or sulfides with garnet or perovskite structures.
4. The dry masterbatch as described in claim 3, characterized in that, The oxide with lithium-ion conductivity is selected from lithium aluminum germanium phosphate and lithium aluminum titanium phosphate with NASICON structure.
5. The dry masterbatch as described in claim 1, characterized in that, in When the ceramic particles are composed of LAGP, the LAGP is selected from Li 1+x Al x Ge 2-x (PO4)3 or Li 1+x+y Al x Ge 2-x-y-z M y N z (PO4)3; When the ceramic particles are composed of LATP, the LATP system is selected from Li 1+x Al x Ti 2-x (PO4)3, or Li 1+x+y Al x Ti 2-x-y- z M y Nz(PO4)3; Where x is between 0.1 and 0.8, y is between 0 and 0.2, and z is between 0 and 0.2; where M is a trivalent cation and N is a tetravalent cation.
6. The dry masterbatch as described in claim 5, characterized in that, The trivalent cation is selected from Sc 3+ Y 3+ Ga 3+ In 3 + La 3+ Furthermore, the tetravalent cation is selected from Zr. 4+ Si 4+ Sn 4+ .
7. The dry masterbatch as described in claim 3, characterized in that, The oxide with a garnet or perovskite structure is selected from lithium lanthanum zirconium oxide or lithium lanthanum titanium oxide.
8. The dry masterbatch as described in claim 1, characterized in that, When the ceramic particles are composed of LLZO material, the LLZO material is selected from at least one of LLZO, Ga-LLZO, Cu-LLZO, Ta-LLZO, Sr-LLZO and Al-LLZO.
9. The dry masterbatch as described in claim 3, characterized in that, The sulfide is selected from LPSC.
10. The dry masterbatch as described in claim 1, characterized in that, The weight ratio of the plurality of positive electrode particles to "the polymer material and the lithium salt" to "the conductive agent and the plurality of ceramic particles" is 88~97:10~2:2~1.
11. The dry masterbatch as described in claim 1, characterized in that, The polymer material may also include either PVA or HDPE.
12. The dry masterbatch as described in claim 1, characterized in that, The multiple conductive agents are selected from at least one of carbon nanotubes, nanoscale amorphous carbon, and graphene.
13. The dry masterbatch as described in claim 1, characterized in that, The lithium salt is selected from either PDDA-TFSI or Py14-TFSI.
14. The dry masterbatch as described in claim 13, characterized in that, The lithium salt may also include at least one of LiBOB, Li3PO4, LiFSI, LiTFSI, and LiPF6.
15. The dry masterbatch as described in claim 1, characterized in that, The positive electrode substrate is an aluminum foil substrate.